Dissemination of the AHCPR clinical practice guideline in community health centres. Issue 4 (1st December 2002) - DePue, J D; Goldstein, M G; Schilling, A; Reiss, P; Papandonatos, G; Sciamanna, C; Kazura, A
Abstract : Objective: To evaluate dissemination of the Agency for Health Care Policy and Research (AHCPR) Smoking cessation clinical practice guideline in community health centres. Design: Pre- and post-trial. Setting: Fourteen community health centres in Rhode Island. Subjects: Provider performance was assessed with 1798 and 1591 patient contacts, in pre-post cross sectional consecutive samples, respectively, and 891 contacts at one year follow up. Interventions: Three, one hour on-site provider training sessions, on review of effective tobacco interventions, use of office systems, and tobacco counselling skill building. Outcome measures: Chart documentation of four A's (Ask, Advise, Assist, and Arrange follow up) at most recent primary care visit. Results: While average performance rates increased for Ask and Advise (from 30% to 44%, and 19% to 26%, pre-post, respectively), significant increases were found only for some visit types, with further differences by patient sex. There were significant increases for Ask for all except obstetric/gynaecological (ob/gyn) visit types. Patients at yearly physicals and first visits were more likely to be asked at all time points, while males were more likely to be asked at acute visits than were females. There were no significant increases for Advise, Assist, and Arrange across time, although female patients showed a differential increase in Advise post-training. Advise was significantly more likely in yearly physicals and first visits, and less likely in ob/gyn visits, at all time points. Conclusions: This guideline dissemination effort resulted in quite different provider counselling rates across patient sexes, and visit types. Guideline implementation may require more sustained efforts, with multiple strategies, which are reinforced at higher policy levels, to more fully integrate tobacco interventions into routine primary care practice with all patients who smoke.